A cluster of X-linked miRNAs are de-repressed with age in mouse liver and target growth hormone signaling - Petrashen, Anna P.; Lin, Yufei; Kun, Bianca; Kreiling, Jill A. (Frontiers in Aging, 2023)
Growth hormone (GH) signaling influences lifespan in a wide variety of mammalian species.We previously reported that a cluster of miRNAs located on the X-chromosome are derepressed with age in male mouse liver, and a subset, the mir-465 family, can directly attenuate expression of the growth hormone receptor (GHR) in vitro leading to a reduction in GH signaling. Here we show that this cluster of miRNAs is also upregulated in the liver with age in females, and that calorie restriction and the Ames dwarf genotype, both known to delay aging, attenuate the upregulation of the miRNA cluster. Up-regulation of mir-465 in vivo leads to a reduction in GHR mRNA in the liver and an attenuation of GH signaling, indicated by a reduction in GHR, IGF-1, IGFBP3, and ALS mRNA expression. There is a corresponding reduction in IGF-1 protein levels in the liver and plasma. These results suggest that the age-associated upregulation of the X-chromosomal cluster of miRNAs could influence lifespan.